Genetic variablity in ginger (Zingiber officinale Rosc.) - YADAV, R K (Journal of Spices and Aromatic Crops, 1999)
The coefficient of variation, heritability and expected genetic advance for 18 important horticultural traits was estimated in 26 accessions of ginger (Zingiber officinale) at Raigarh District, Madhya Pradesh. The genotypic coefficient of variation was high for length and weight of secondary rhizome, weight of primary rhizome, number of secondary and primary rhizomes and rhizome yield per plant. High heritability coupled with high genetic advance as percentage of mean was observed for plant height, leaf length, suckers per plant, number of mother and secondary rhizomes, weight of primary rhizome and rhizome yield per plant indicating that desirable improvement in these traits can be brought about through straight selection.